2018
DOI: 10.1192/bja.2018.27
|View full text |Cite
|
Sign up to set email alerts
|

Sexual boundary violations: victims, perpetrators and risk reduction

Abstract: SUMMARYSexual boundary violations by healthcare professionals is a subject that has largely been ignored in the UK. There has been little research into the field. It is rarely taught on professional training courses and practitioners appear to know very little about it. The history of sexual boundary violations is littered with failures to notice, failures to report and inadequate justice for victims and perpetrators alike. Perpetrators are commonly assumed to be predators. Given the many widely reported recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
3
10
0
1
Order By: Relevance
“…In our study, mental health practitioners had three times the risk of complaint regarding sexual boundary breaches compared with physical health practitioners. High rates of concern about sexual misconduct by psychiatrists and psychologists are a consistent finding in previous studies of complaints,11 regulatory actions6 10 12 and self-reported behaviour 7 37. Compared with comparator professions in this study, the day-to-day practice of mental health practitioners more often involves being alone with patients behind closed doors, discussing more personally-intimate information, for longer periods of time.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, mental health practitioners had three times the risk of complaint regarding sexual boundary breaches compared with physical health practitioners. High rates of concern about sexual misconduct by psychiatrists and psychologists are a consistent finding in previous studies of complaints,11 regulatory actions6 10 12 and self-reported behaviour 7 37. Compared with comparator professions in this study, the day-to-day practice of mental health practitioners more often involves being alone with patients behind closed doors, discussing more personally-intimate information, for longer periods of time.…”
Section: Discussionsupporting
confidence: 88%
“…We devote much of this article to adverse idealising transferences (AITs) – the adverse effects that may arise when a patient transfers idealising feelings onto the professional – because, although we have found it to be a significant factor in most cases of harm, it is rarely discussed in the literature on harm. Our second article (Hook 2018) will focus specifically on sexual boundary violations – the assessment and management of victims and perpetrators and proposals for reducing risk.…”
mentioning
confidence: 99%
“…In relation to doctors as carers, Vaillant et al (1972) were possibly the first to suggest that behavioural problems in doctors might be related to their relationships with their fathers. In their second article Hook & Devereux (2018b) cite the study by MacDonald et al (2015) which found high levels of insecurity of attachment in doctors referred to a therapy programme for professional boundary violations. Insecure attachment might explain the adverse idealising transference described by Hook & Devereux (2018a), because idealisation is a key aspect of dismissing/avoidant attachment strategies.…”
Section: Dysfunctional Attachment Stylesmentioning
confidence: 99%
“…I am grateful to both the Editor of BJPsych Advances and to the authors of these two stimulating articles (Hook 2018a,b) for an opportunity to reflect on this most important of topics. Reading these articles reminded me of a conversation about sexual boundary violations by therapists that I had in 1990 with a senior and highly respected professor of psychiatry who was a leader in mental health ethics.…”
mentioning
confidence: 99%